Expertise of salesperson influence customer purchase decision: A case study on Kemudi Timur Elektronik Sdn Bhd / Nor Hasniah Che Sulaiman - Che Sulaiman, Nor Hasniah (2014)
This study was conducted to fulfill the requirement needed for Faculty of Business Management, UiTM. The topic has selected by researcher entitled “Expertise of Salesperson Influence Customer Purchase Decision” using KEMUDI TIMUR ELEKTRONIK SDN BHD as case study. Specifically, this study is conducted to identify the relationship between expertise of salesperson (competence, power of convince and credibility) on customer purchase decision. It was previously reported that competence, power of convince and credibility of salesperson fit to have a significant relationship with the customer purchase decision. Therefore, the focus of this study is to discover whether similar relationships do exist among the expertise of salesperson and customer purchase decision. A quantitative method was employed and data were collected using questionnaires. There were 100 questionnaires are distributed to respondents. To estimate the function related to variables involved in independent variables (competence, power of convince and credibility), the researcher uses multiple linear regression analysis. The results revealed significant relationships exist between competences, power of convince and credibility fit with the customer purchase decision. At the same time, this study fulfills the researcher’s objectives which are to identify the relationship between salesperson’s competence and customer purchase decision. Second, to identify the relationship between salesperson’s power of convince and consumer purchase decision. The last objectives which are to identify the relationship between salesperson’s credibility and customer purchase decision